Pengaruh Sistem Informasi Akuntansi, Gaya Kepemimpinan Dan Kompensasi Terhadap Kinerja Karyawan Pada PT. Indo Metro Surya Andola Kota Metro Lampung - Sasmita, Izmi Aren; Zanaria, Yulita; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
The purpose of this study was to test whether the Accounting Information System, Leadership Style and Compensation at PT. Indo Metro Surya Andola Lampung Province Metro City can affect Employed Performance. The theory used in this study is the Theory Acceptance Model (TAM), the theory of Leadership Behavior and the Equity Theory. This type of research uses quantitative methods. The quantitative method is to emphasize the analysis on numerical data (numbers) which are processed by statistical methods. The population in this study were 72 service employees. The data analysis technique used is statistical description of the validity and realibility of the data, classical assumptions, multiple linear regression analysis, t/partial test, statistical f test (simultaneous), coefficient of determination and statistical hypothesis using the SPSS (Statistic Package And Social Science) application 26.0 for Windows. The results of this study indicate that partially Accounting Information System and Compensation have a significant effect on Employee Performance. While Leadership Style does not significantly affect Employee Performance. Simultaneously or simultaneously Accounting Information Systems, Leaderrship Styles and Compensation have a significant effect on Employee Performance